2001
DOI: 10.1080/000164801300006209
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Storage of Adenosine Triphosphate in the Guinea-pig Cochlear Lateral Wall and Concentrations of ATP in the Endolymph during Sound Exposure and Hypoxia

Abstract: Previous studies have revealed putative vesicular stores of adenosine triphosphate (ATP) in the marginal cells of the cochlear stria vascularis which may serve as a source of ATP for purinergic signalling. This study aimed to provide further evidence of ATP storage in the cochlea and to see whether ATP levels in the endolymph are affected by noise and hypoxia. Tissues from the lateral wall and organ of Corti of the guinea-pig cochlea were fractionated to obtain vesicular (VF) and mitochondrial (MF) fractions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 16 publications
(19 reference statements)
2
37
0
Order By: Relevance
“…Previous studies have suggested that this increase in [Ca 2+ ] i is due in part to ATP release from connexin-based hemichannels [26]. Changes in [Ca 2+ ] i were measured in response to 103 dB SPL 1000 Hz sound in the presence of 40 U/l apyrase, to eliminate exogenous ATP stimulation, 100 μM CBX, to inhibit ATP release into the apical compartment through connexin hemichannels, 1 μM thapsigargin, an inhibitor of SERCA, which clears intracellular Ca 2+ through uptake into endoplasmic reticular stores, and 1 mM gentamicin, a blocker of mechanoelectrical transduction channels (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that this increase in [Ca 2+ ] i is due in part to ATP release from connexin-based hemichannels [26]. Changes in [Ca 2+ ] i were measured in response to 103 dB SPL 1000 Hz sound in the presence of 40 U/l apyrase, to eliminate exogenous ATP stimulation, 100 μM CBX, to inhibit ATP release into the apical compartment through connexin hemichannels, 1 μM thapsigargin, an inhibitor of SERCA, which clears intracellular Ca 2+ through uptake into endoplasmic reticular stores, and 1 mM gentamicin, a blocker of mechanoelectrical transduction channels (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
“…In adult guinea pigs, noise exposure is associated with an acute increase in endolymphatic ATP levels [2], raising the possibility that ATP release into scala media is an early event in noise-induced ototoxicity. This finding was bolstered by a series of studies in neonatal organotypic mouse cochlear cultures implicating intracellular Ca 2+ signaling (ICS) waves in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Noise trauma results in depletion of intracellular ATP as well as in changes in vascular permeability [28]. The link between ATP depletion and permeability changes is the decreased Na + /K + -ATPase activity that ATP depletion engenders [29].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which noise exposure decreases Na + /K + -ATPase activity is thought to be through depletion of regional ATP or through direct affects on the structure of the enzyme [54]. Impaired energy metabolism, accompanied by rapid depletion of intracellular ATP, has been reported in noise-exposed animals [28]. As ATP is the prime substrate of the Na+/K+ pump, reduced ATP levels may have the effect of depressing Na + /K + -ATPase activity, leading to PKCη activation and occludin hyperphosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analysis showed that ATP was secreted and consumed by anemones after hair bundle disruption, and that RP displayed ATPase activity, although the precise function of ATP in the repair process in not clear [32]. Currently, the possible role of ATP in vertebrate hair cell repair after sub-lethal trauma is also unknown, although ATP is present in the endolymph after noise trauma [33] and has known neurohumoral and apoptotic signaling functions [34]. …”
Section: Introductionmentioning
confidence: 99%